Isolation of novel phytoconstituents from the stem part of Cleome gynandra Linn and their antimicrobial activity - Ranjitha J; Madonna Shalma; Michael Donatus; Vijayalakshmi S (International Journal of Phytomedicine, 2014)
Dried and powdered stem of Cleome gynandra Linn were extracted with methanol and chloroform solvents. From the extract, four individual components were identified using UV-Visible Spectrophotometer, FT-IR, GC-Mass and NMR technique. The extracted components were isolated as pure form using Silicagel-G column chromatography. Identity of these four novel compounds such as β-amyrin, β -Amyrin-3-O- β-Glucopyranoside, Stigmasetrol and Sitosterol was confirmed by spectral interpretation. These compounds were tested for their antimicrobial activity and showed inhibition against all the tested bacterial and fungal cultures.